Outcomes of Children With Suspected Appendicitis and Incompletely Visualized Appendix on Ultrasound. (May 2014) - Ross, Marshall J.; Liu, Helena; Netherton, Stuart J.; Eccles, Robin; Chen, Ping‐Wei; Boag, Graham; Morrison, Ellen; Thompson, Graham C.; Gorelick, Mark H.
Abstract Objectives The objective was to review the clinical outcomes of children with suspected appendicitis after an ultrasound (US) examination fails to fully visualize the appendix, the diagnostic characteristics of US in children with suspected appendicitis, and the predictive value of secondary signs of appendicitis when the appendix is not fully visualized. Methods This was a retrospective health record review of children aged 3 to 17 years presenting to a tertiary pediatric emergency department (ED) with suspected appendicitis. Descriptive statistics and diagnostic test characteristics are reported. Results Overall, 968 children had US. The appendix was fully visualized in 442 cases (45.7%), and 526 (54.3%) children had incompletely visualized appendices. The disposition of those with incompletely visualized appendices were as follows: 59.1% were discharged home, 10.5% went directly to the operating room, and 30.4% were admitted to the hospital for further observation. Of those discharged home based on clinical findings after incompletely visualized appendices, fewer than 0.3% ended up having appendicitis. Ultimately 15.6% of children with incompletely visualized appendices had pathology‐confirmed appendicitis. The sensitivity and specificity of US for children with fully visualized appendices were 99.5% (95% confidence interval [CI] = 96.7% to 100%) and 81.3% (95% CI = 75.2% to 86.2%), respectively. The sensitivity and specificity for the presence of any secondary sign in diagnosing appendicitis were 40.2% (95% CI = 29.6% to 51.7%) and 90.6% (95% CI = 87.5% to 93.2%), respectively. Conclusions Children with incompletely visualized appendices on US can be safely discharged home based on clinical findings with an acceptable rate of missed appendicitis. Children with nonreassuring clinical examinations following incompletely visualized appendices on US may benefit from further imaging studies prior to appendectomy, to reduce the rate of negative appendectomy. While the presence of secondary signs of inflammation can be used to rule in appendicitis, statistical strength to rule out appendicitis in the absence of secondary signs is insufficient.